DNA vaccination boosts Bacillus Calmette–Guérin protection against mycobacterial infection in zebrafish. Issue 1 (January 2016) - Oksanen, Kaisa E.; Myllymäki, Henna; Ahava, Maarit J.; Mäkinen, Leena; Parikka, Mataleena; Rämet, Mika
Abstract: Despite the widespread use of the current Bacillus Calmette–Guérin (BCG) vaccine, tuberculosis is still a major cause of morbidity and mortality worldwide. Vaccination with BCG does not prevent a Mycobacterium tuberculosis infection, nor does it inhibit the reactivation of latent tuberculosis. Here, we show that adult zebrafish are modestly and variably protected from a mycobacterial infection by BCG vaccination. An intraperitoneal (i.p.) BCG vaccination was associated with enhanced survival upon a high-dose (20, 000 bacteria) Mycobacterium marinum infection. In addition, BCG-vaccinated fish were more able to restrict a low-dose (30 bacteria) intraperitoneal infection with M. marinum, as indicated by lower bacterial loads at six weeks post infection (wpi). However, the vaccination could not completely prevent an infection. A qRT-PCR analysis comparing BCG-vaccinated and unvaccinated fish upon a mycobacterial infection indicated that the induction of Tumor necrosis factor ( TNF ) was more modest in vaccinated fish. The partial protection gained by BCG could be boosted by a DNA vaccine combining Ag85B, ESAT6 and a resuscitation-related gene RpfE, suggesting that this combination of antigens could be useful for a future BCG booster vaccine. We conclude that zebrafish is a useful early-phase preclinical model for studying subunit vaccines designed for boosting the effects of BCG. Highlights: A novel vaccine for boosting or replacing Bacillus Calmette–Guérin (BCG) is needed. Adult zebrafish is a well-established model for studying mycobacterial infection. BCG vaccination variably protects zebrafish against mycobacterial infection. BCG-induced protection in zebrafish can be boosted with a DNA-based vaccine. Zebrafish is a promising model for pre-clinical tuberculosis vaccine research.